2022
DOI: 10.1039/d2en00297c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel slow-release nanourea/chitosan nanocomposite and its effect on Vigna radiata L.

Abstract: Nano-fertilizers play a significant role in sustainable agriculture. In the present work, a new formulation of coated nanourea has been proposed for the slow and sustainable release of nitrogen. Bare...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Another study reported that nitrogen from urea coupled with humic acid aided in the root growth and construction in sweet potato which resulted in improved biomass and plant yield [44]. Similar to the ndings here, using nanourea coupled with chitosan, another study reported the enhanced effects in root length in Vigna radiata [11].…”
Section: Early Effects Of Tnu On Seedling Germination and Growthsupporting
confidence: 83%
See 1 more Smart Citation
“…Another study reported that nitrogen from urea coupled with humic acid aided in the root growth and construction in sweet potato which resulted in improved biomass and plant yield [44]. Similar to the ndings here, using nanourea coupled with chitosan, another study reported the enhanced effects in root length in Vigna radiata [11].…”
Section: Early Effects Of Tnu On Seedling Germination and Growthsupporting
confidence: 83%
“…Recently, using nanomaterials, several studies have reported the development of different types of combinations for delivering urea/nitrogen to plants by incorporating the cargo carrier approaches. In a study by Sharma et al (2022), nanocomposite of urea and chitosan was synthesised to work as a slowrelease fertiliser and showed enhanced plant growth effects in Vigna radiata [11]. Using chitosan as a carrier, in another study by Saad et al (2022), nitrogen was delivered to wheat plants to observe bene cial effects on plants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such a sustained nutrient supply is instrumental in fostering the development of a robust root system, which is pivotal for the overall health and resilience of plants in later stages ( Wang et al., 2020 ). The inception of nanofertilizers, particularly formulations, such as coated nanourea, accentuates the fusion of technology with traditional farming practices ( Sharma et al., 2022 ). The observed enhancement in parameters, such as root and shoot length, photosynthetic pigments, and antioxidative capabilities in plants treated with nanourea/chitosan nanocomposites, as opposed to bare nanourea or commercial urea, indicates the potential of these novel fertilizers.…”
Section: Nutrition and Water Management In Agriculture Farming System...mentioning
confidence: 99%
“…Reports have been published on a wide range of potential applications in the agroenvironmental sector, such as agrochemical delivery [11], nanofertilisers [12], improved stress tolerance [13], nanopesticides [14], soil protection [15], food packaging [16] and contaminant removal [17], amongst others. In general, the benefits of the use of nanotechnology would include a reduction in the use of scarce resources such as, for example, a 50% saving in the use of water for growing Egyptian clover (Trifolium alexandrinum) under desert conditions with the use of a nanoclay soil amendment [18], a reduction in environmental damage such as a study that demonstrated a reduction in nitrogen leaching of up to 55% using nanocomposite nanourea in the cultivation of mung beans (Vigna radiata L.) [19], and a reduction in the amount of agrochemical required for crop protection such as a study in which nanoemulsions containing the pesticide abamectin demonstrated a 50% lethal concentration (LC 5 0) nearly five times less than the emulsifiable concentrate of the same chemical against diamondback moth (Plutella xylostella) larvae [20]. Of particular interest for this review would be the utilisation of nanotechnology for the detection and analysis of a wide range of analytes.…”
Section: Introductionmentioning
confidence: 99%